2012
DOI: 10.1128/jb.01861-12
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Bacillus thuringiensis Serovar Sichuansis Strain MC28

Abstract: cBacillus thuringiensis is an important microbial insecticide used in the control of agricultural pests. Here we report the finished, annotated genome sequence of Bacillus thuringiensis serovar Sichuansis strain MC28, which can form parasporal crystals consisting of Cry4Cc1, Cry30Fa1, Cry53Ab1, Cry54Aa1, Cry54Ab1, Cry68Aa1, Cry69Aa1, Cry69Aa2, Cry70Ba1, Cyt1Da1, and Cyt2Aa3. It is also highly toxic to lepidopterous and dipterous insects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 6 publications
(3 reference statements)
0
14
0
Order By: Relevance
“…We hypothesize that these toxins may be toxic to dipteran insects since they are contained within dipteran subnetworks. Actually, Cry29A was reported to synergize the toxicity of Cry11Bb against Aedes aegypti (Diptera: Culicidae), and Cry50Aa, Cry50Ba, Cry54Ba, Cry68Aa, and Cry70Aa were all found in some strains with high toxicity against mosquitoes ( 52 55 ). Similarly, in the coleopteran subnetwork, Cry26 and Cry28 had no reported toxicity; we suspect that they may target coleopteran hosts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that these toxins may be toxic to dipteran insects since they are contained within dipteran subnetworks. Actually, Cry29A was reported to synergize the toxicity of Cry11Bb against Aedes aegypti (Diptera: Culicidae), and Cry50Aa, Cry50Ba, Cry54Ba, Cry68Aa, and Cry70Aa were all found in some strains with high toxicity against mosquitoes ( 52 55 ). Similarly, in the coleopteran subnetwork, Cry26 and Cry28 had no reported toxicity; we suspect that they may target coleopteran hosts.…”
Section: Discussionmentioning
confidence: 99%
“…In CT-43 and HD-1, five toxins were encoded by genes from two different plasmids, with four of them on the larger one and the other on a smaller one, respectively ( 58 ). In MC28, 11 toxin genes were contained by three different plasmids ( 53 ), and in IS5056, nine toxins were encoded by genes on four different plasmids ( 59 ). The range of loci encoding toxins implies that multiple toxins in the same genome were gained by multiple independent HGT events.…”
Section: Discussionmentioning
confidence: 99%
“…Because the genome data available for the B. cereus sensu lato group in NCBI include 50 B. thuringiensis , 161 B. cereus and 93 B. anthracis strains annotated according to previously reported insecticidal activities and serotypes, we divided the 50 B. thuringiensis strains into three groups: highly, generally and weakly toxic strains (12, 29 and 9 strains, respectively, Table 1 and Supplementary Table S2 ). The comparison showed that the B. thuringiensis strains with high insecticidal toxicity 10 12 19 had significantly larger genome sizes and were richer in plasmid content than the weakly toxic B. thuringiensis strains, and typical B. cereus , B. anthracis strains which are not toxic to insects (P < 0.05, T-test, Fig. 1A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that B. thuringiensis possessed a complicated pathogenic mechanism. Due to the rapid development of high-throughput sequencing technology, many B. thuringiensis genomes have been completed in recent years 9 10 11 12 13 14 15 16 . However, with the exception of two draft genomes of Btk 17 18 , no complete genomes of the biopesticide production strains (especially Btk HD-1 and similar strains) are currently available.…”
mentioning
confidence: 99%
“…During sporulation, the gram-positive bacterium Bacillus thuringiensis (Bt) produces crystalline inclusions consisting of δ-endotoxins (Cry or Cyt proteins) with insecticidal activity 1 . Genomic analysis has contributed to the identification of new genes coding for toxins that are active against different insect species including orders such as Lepidoptera, Diptera [2][3][4][5][6][7] , and Coleoptera 8 . Proteins with nematicidal [9][10][11] and molluscicidal 12 activities have also been described.…”
mentioning
confidence: 99%